Silariang : Cinta yang Terhalang - Indrayanti Indrayanti; Imelda Duma (Jurnal Komunikasi Korporasi dan Media (JASIMA), 2020)
Silariang (kawin lari) is a very shameful thing in Makassar's Bugis culture. Silariang is a social problem that is prone to conflict and clashes between families that often have to be paid for with the lives of those who do it, both women and men. Women's familiesexperience self-suffering (family disgrace), while men who are considered the cause of women's family disgrace are called tomannyala. This study used a qualitative method with in-depth interviews with three married couples who did cross-sectional. The purpose of this research is what is the reason behind doing the cross-sectional and how to solve it. This study found a variety of behavioral reasons. The first reason is due to economic factors where the men are unable to provide the dowry needed by the women's families. Anotherreason is that one of the parties must marry based on the family order of the woman, and the acceptable way for them is known as abaji', namely remarrying by preparing a dowry (pannai) but smaller and paying a fine (pappasala) of 20 Riyal as an absolute requirement.